P356Dynamic nature of the methylation landscape of the heart. (15th July 2014) - Greco, CM; Kunderfranco, P; Carullo, P; Papait, R; Condorelli, G
Abstract: Cardiac hypertrophy is associated with significant transcriptional changes characterized by the re- expression of fetal genes. Epigenetic mechanisms play a key role in defining the gene expression profile without modifying the actual DNA sequence. Recently, DNA methylation has been found to play a role in gene transcription regulation during heart failure, indicating that DNA methylation in the heart is a dynamic process. DNA methylation has been considered to be a stable modification that could only be removed by passive mechanisms during DNA replication. However, an active DNA de-methylation mechanism involving the hydroxylation of 5-methylcytosine (5-mC) to 5-hmC has emerged. Given the post-mitotic nature of cardiomyocytes, active de-methylation is likely to be involved in the dynamicity of the cardiac methylome. Nevertheless, the presence and possible function of 5-hmC in the heart has not been investigated yet. Therefore, we analyzed the genome-wide transcription and methylation/hydroxymethylation status of cardiomyocytes isolated from embryonic, neonatal, adult and hypertrophic (1 week pressure-overloaded) mouse heart with RNA, MeDIP and hMeDIP (5-mC/5-hmC DNA immunoprecipitation) high-throughput sequencings. We found that genomic regions enriched in 5-hmC were profoundly dynamic: in particular, adult cardiomyocytes were significantly enriched in 5-hmC at gene bodies, and hypertrophy was associated with a shift of this mark to intergenic regions and repetitive elements, recapitulating the landscape found in embryonic cardiomyocytes. We then assessed if there was a relationship between 5-hmC and gene transcription, as previously described for neurons. We found that the presence of 5-hmC at both promoter regions and gene bodies was associated with high levels of transcription. Moreover, integrative analysis of previously generated ChIP-seq data revealed a genome-wide strong co-localization of 5-hmC with active histone marks. Gene ontology analysis of genes harboring 5-hmC uncovered distinct gene sets for biological processes, molecular function and KEGG signature in embryonic, neonatal, adult and hypertrophic cardiomyocytes. Finally, differential analysis during the hypertrophic response revealed a strong enrichment of 5-hmC on a set of repetitive elements, which were also characterized by loss of H3K9me3, and contained a predicted binding site for cardiac specific transcription factors. Our study offers the first comprehensive analysis of 5-hmC in cardiomyocytes, and provides evidence that this epigenetic mark plays an important role in the heart under normal and stressed conditions.